College entrance exams: A modern "shibboleth"?. Issue 3 (24th May 2022) - Robinson, Daniel; Wainer, Howard
Abstract : The Covid‐19 pandemic led many US colleges to drop requirements for admissions tests. Daniel Robinson and Howard Wainer consider what the consequences of this decision might be – for students and universities Abstract : The Covid‐19 pandemic led many US colleges to drop requirements for admissions tests. Daniel Robinson and Howard Wainer consider what the consequences of this decision might be — for students and universities.